2021
DOI: 10.3389/fmed.2021.650369
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physician's Knowledge of Potential Drug-Drug Interactions: An Online Survey in China

Abstract: Background: Drug interactions are the most common preventable cause of adverse drug reaction, which may result in drug toxicity or undesired therapeutic effect with harmful outcomes to patients. Given the rising use of combination therapies, the main objectives of this study were to estimate the degree to which physicians can identify potential drug-drug interactions (PDDIs) correctly and to describe the common source of information used by physicians when they need to check PDDIs.Methods: A cross-sectional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In China, one of the world's largest pharmaceutical markets, physicians DDI knowledge levels were evaluated in 2019. However, the physicians' knowledge in the study was inadequate (Yuan et al, 2021). Ko and authors (2008) found prescribers' knowledge of potential DDIs insufficient.…”
Section: Discussionmentioning
confidence: 87%
“…In China, one of the world's largest pharmaceutical markets, physicians DDI knowledge levels were evaluated in 2019. However, the physicians' knowledge in the study was inadequate (Yuan et al, 2021). Ko and authors (2008) found prescribers' knowledge of potential DDIs insufficient.…”
Section: Discussionmentioning
confidence: 87%
“…This may be due to reporters' lack of knowledge about colchicine's drug interaction potential, resulting in an increased exposure to interacting drugs. 36,37 Physicians' lack of knowledge of drug interactions has been reported, and the common overriding of alerts reduces the effectiveness of DDI alerting software. 37,38 Our results suggest that colchicine adverse outcomes when concomitantly administered with a CYP3A4/P-gp inhibitor are of clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yuan et al conducted an online DDI survey focused on physicians and reported that physicians had an unsatisfactory knowledge level about clinically significant DDI (correctly classified 33.4% of DDIs). [ 22 ] Also, Nabovati et al found that medical residents of 22 specialties correctly classified the DDI as only 41%. [ 23 ] Thus, medical education about DDI since undergraduate degree and residency training could be essential, including introducing an accessible electronic DDI database that might help physicians recognize DDI before prescribing medication to their patients.…”
Section: Discussionmentioning
confidence: 99%